Genomic Data Mining Reveals Abundant Uncharacterized Transporters in Coccidioides immitis and Coccidioides posadasii - Hong Cai; Hao Zhang; Daniel H. Guo; Yufeng Wang; Jianying Gu (Journal of Fungi, 2022)
Coccidioides immitis and Coccidioides posadasii are causative agents of coccidioidomycosis, commonly known as Valley Fever. The increasing Valley Fever cases in the past decades, the expansion of endemic regions, and the rising azole drug-resistant strains have underscored an urgent need for a better understanding of Coccidioides biology and new antifungal strategies. Transporters play essential roles in pathogen survival, growth, infection, and adaptation, and are considered as potential drug targets. However, the composition and roles of transport machinery in Coccidioides remain largely unknown. In this study, genomic data mining revealed an abundant, uncharacterized repertoire of transporters in Coccidioides genomes. The catalog included 1288 and 1235 transporter homologs in C. immitis and C. posadasii, respectively. They were further annotated to class, subclass, family, subfamily and range of substrates based on the Transport Classification (TC) system. They may play diverse roles in nutrient uptake, metabolite secretion, ion homeostasis, drug efflux, or signaling. This study represents an initial effort for a systems-level characterization of the transport machinery in these understudied fungal pathogens.